#### Answer

$ x= 1 , -7$

#### Work Step by Step

$x(x+6) = 7$
$x^2 + 6x = 7$
$x^2 + 6x - 7 = 7 - 7$
$x^2 + 6x - 7 = 0$
$x^2 - x + 7x - 7 = 0$
$x ( x - 1) + 7( x- 1)= 0$
$(x-1) ( x + 7) = 0$
Therefore
$x-1 = 0$
$x = 1$
OR
$x+7 = 0$
$ x= -7$

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

$ x= 1 , -7$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.